THE PORIFERA, CNIDARIA, BRYOZOA, AND ECHINODERMATA COLLECTIONS OF THE UNIVERSIDADE FEDERAL DO CEARÁ: CONTRIBUTIONS TO THE MARINE BIODIVERSITY KNOWLEDGE OF NORTHEASTERN BRAZIL: As coleções de Porifera, Cnidaria, Bryozoa e Echinodermata da Universidade Federal do Ceará: contribuições para o conhecimento da biodiversidade marinha do Nordeste do Brasil - Barroso, Cristiane Xerez; Salani, Sula; Arruda, Mariany Oliveira; Queiroz Monteiro da Silva, Maiara; Silva, Marcos Vieira da; Matthews-Cascon, Helena (Arquivos de Ciências do Mar, 2022)
In the last years, in addition to recording the diversity, the biological collections have also been used as repositories for ecological data. In order to contribute to the knowledge of Brazilian biological collections and, consequently, Brazil’s biodiversity, especially marine, the present study brings data from four regional collections (phyla Porifera, Cnidaria, Bryozoa, and Echinodermata) of the Departamento de Biologia, Universidade Federal do Ceará. The composition and geographic distribution data of each phylum were obtained by analyzing the digital spreadsheets containing the information about the deposited material. Together, the analyzed collections have 1,378 lots, being 303 of Porifera, 131 of Cnidaria, 414 of Bryozoa, and 530 of Echinodermata. Despite their regional nature, the collections of Porifera, Cnidaria, Bryozoa and Echinodermata of the Universidade Federal do Ceará represent, respectively, 6.5%, 6.9%, 10.7%, and 17.5% of the species so far recorded for the Brazilian coast. Although regional biological collections can help to better understand the diversity, there has never been a long-term policy formation and maintenance of scientific collections in Brazil. The preservation of these repositories, together with the sharing of their knowledge, will allow for more appropriate conservation decision-making in local, regional, and global scales. Keywords: biological collections, sponges, cnidarians, bryozoans, echinoderms.